Three times out of Asia Minor: the phylogeography of Arabis alpina L. (Brassicaceae) - Koch, Marcus (Molecular ecology, 2006)
Arabis alpina is a characteristic plant in arctic-alpine habitats and serves as a classical example to demonstrate biology, ecology and biogeography of arctic-alpine disjuncts. It has a wider distribution than most other arctic-alpine plants, covering all European mountain systems, the Canary Islands, North Africa, the high mountains of East Africa and Ethiopia, the Arabian Peninsula and mountain ranges of Central Asia in Iran and Iraq. Additionally it is found in the northern amphi-Atlantic area including northeastern North America, Greenland, Iceland, Svalbard and northwestern Europe. We used markers from the nuclear (internal transcribed spacer of ribosomal DNA) and chloroplast genome (trnL-F region) to reconstruct its phylogeographic history. Both markers revealed clear phylogeographic structure. We suggest that A. alpina originated in Asia Minor less than 2 million years ago based on synonymous mutation rates of different genes (plastidic matK, nuclear adh and chs). From the Asian ancestral stock one group migrated via the Arabian Peninsula to the East African high mountains. A second group gave rise to all European and northern populations, and also served as source for the northwest African populations. A third group, which is still centred in Asia, migrated independently southwards and came into secondary contact with the East African lineage in Ethiopia, resulting in high genetic diversity in this area. In the Mediterranean regions, the genetic diversity was relatively high with numerous unique haplotypes, but almost without geographic structure. In contrast, the populations in the northern amphi-Atlantic area were extremely depauperate, suggesting very recent (postglacial) expansion into this vast area from the south.
Gesehen am 09.05.2017